1994
DOI: 10.1093/rheumatology/33.6.541
|View full text |Cite
|
Sign up to set email alerts
|

Original Clinical Papers: Longitudinal Bone Mineral Density Changes in Early Rheumatoid Arthritis

Abstract: A prospective longitudinal study of patients with early RA was performed to examine the influence of disease duration, disease activity and physical activity on bone loss. Sixty-seven patients with non-steroid treated RA of less than 5 yr duration, including 16 patients with disease duration less than 6 months, had BMD measurements of the femoral neck and the lumbar spine over a 12-month period using dual energy X-ray absorptiometry. The BMD changes were compared with values from 72 control patients and were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
2
5

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 0 publications
1
28
2
5
Order By: Relevance
“…RA is known to cause a generalized skeletal effect, with bone loss in the femoral neck and lumbar spine (7,8); however, a recent cross-sectional study has shown that changes in hand bone mass are more dramatic than changes at other sites (18), with a reduction in hand bone mineral density of 23%, as compared with 16% at the femoral neck and 11% at the lumbar spine (18). The loss of hand bone mass in patients with RA therefore appears to be a combined result of the generalized plus local effects of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RA is known to cause a generalized skeletal effect, with bone loss in the femoral neck and lumbar spine (7,8); however, a recent cross-sectional study has shown that changes in hand bone mass are more dramatic than changes at other sites (18), with a reduction in hand bone mineral density of 23%, as compared with 16% at the femoral neck and 11% at the lumbar spine (18). The loss of hand bone mass in patients with RA therefore appears to be a combined result of the generalized plus local effects of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Major etiologic factors leading to this bone loss include the direct effect of inflammatory mediators, decrease in physical activity, and corticosteroid treatment (3, 5,6). Recent longitudinal studies have shown significant generalized bone loss within the first few years of disease in patients with RA, which correlated with disease activity (7,8).…”
mentioning
confidence: 99%
“…Shenstone et al (29) reported correlation between BMD and HAQ score, and also showed relationship between lumbar BMD and baseline Stoke Index. The BMD loss was found to be higher in femur neck in early stages of the RA regardless of disease activity and functional loss.…”
Section: Discussionmentioning
confidence: 95%
“…As nossas pacientes apresentaram um tempo médio de doença de 7,73 anos. A perda de massa óssea em coluna lombar e fêmur proximal é descrita em estudos longitudinais, porém a sua relação com o tempo de doença é, às vezes, controversa 22,23 . Nos pacientes cujo tempo de doença é maior que 6 a 12 meses, a perda óssea ocorre de forma mais lenta 22 …”
Section: Discussionunclassified